Stories of social and emotional resilience among pregnant Bangladeshi and Sri Lankan migrant women during COVID-19 lockdowns in Victoria, Australia: A qualitative study using photo-elicitation. - Fathima S.M. Buhary; Meghan A. Bohren; Ashley McAllister; Shahinoor Akter (Elsevier, 2024)
The COVID-19 pandemic disrupted family and community support systems that typically nurture pregnancy and birth experiences of migrant Bangladeshi and Sri Lankan women in Australia. Very little is known about how COVID-19 lockdown measures impacted Bangladeshi and Sri Lankan pregnant women living in Australia during the pandemic. Using an intersectional and resilience thinking approach, we explored the social and emotional resilience of Bangladeshi and Sri Lankan pregnant women living in Victoria, Australia during COVID-19 lockdowns. Semi-structured photo-elicitation interviews were conducted in English, Tamil and Bangla and audio-recorded in-person and virtually. Inductive thematic analysis was used to analyse the visual and oral qualitative data produced. Twenty-five Bangladeshi and Sri Lankan-born women were interviewed. Three key themes emerged from data analysis: challenges exacerbated by COVID-19, sources of social resilience, and sources of emotional resilience. Participants were negatively impacted by closed international borders, care for children, financial pressures of temporary residence and their physical and mental health was impacted. Primary sources of social resilience were derived from family, community and healthcare professional support. Photo data produced by participants depicted patterns of emotional resilience to overcome the challenges of social isolation during their pregnancy in lockdown. The visual and oral data highlighted that participants were significantly impacted by social isolation during COVID-19 lockdowns in Australia. Findings from this study can contribute to understanding how social support networks influence maternity during a pandemic and how culturally safe maternal health practices can be reinforced to support the motherhood of migrant women regardless of visa status.